Flow patterns in the jugular veins of pulsatile tinnitus patients - Kao, Evan; Kefayati, Sarah; Amans, Matthew R.; Faraji, Farshid; Ballweber, Megan; Halbach, Van; Saloner, David (Journal of biomechanics, 2017)
Pulsatile Tinnitus (PT) is a pulse-synchronous sound heard in the absence of an external source. PT is often related to abnormal flow in vascular structures near the cochlea. One vascular territory implicated in PT is the internal jugular vein (IJV). Using computational fluid dynamics (CFD) based on patient-specific Magnetic Resonance Imaging (MRI), we investigated the flow within the IJV of seven subjects, four symptomatic and three asymptomatic of PT. We found that there were two extreme anatomic types classified by the shape and position of the jugular bulbs: elevated and rounded. PT patients had elevated jugular bulbs that led to a distinctive helical flow pattern within the proximal internal jugular vein. Asymptomatic subjects generally had rounded jugular bulbs that neatly redirected flow from the sigmoid sinus directly into the jugular vein. These two flow patterns were quantified by calculating the length-averaged streamline curvature of the flow within the proximal jugular vein: 130.3±8.1m−1 for geometries with rounded bulbs, 260.7±29.4m−1 for those with elevated bulbs (P<0.005). Our results suggest that variations in the jugular bulb geometry lead to distinct flow patterns that are linked to PT, but further investigation is needed to determine if the vortex pattern is causal to sound generation.